Mobilizing Religious Social Capital for Sharia-based Women’s Economic Empowerment in East Java Pesantren: The Agency of Nyai - Moh. Mardi; Khurin In Ratnasari (IQTISHODUNA: Jurnal Ekonomi Islam, 2026)
Despite patriarchal structures in many pesantren, Nyai, female religious authorities within pesantren communities, often function as strategic actors in community economic development. This article analyzes how Nyai mobilizes religious social capital to advance Sharia-based women’s economic empowerment in East Java pesantren. Using an integrative literature review, the study synthesizes scholarly works on pesantren economies, Islamic social entrepreneurship, women’s empowerment, and social capital to identify the mechanisms through which Nyai convert religious legitimacy, trust, kinship ties, alumni networks, and community reciprocity into economic agency. The findings indicate that Nyai’s economic role is not merely supportive or domestic; it operates as a form of faith-based economic governance that strengthens entrepreneurship, cooperative practices, and community resilience. The study contributes to Islamic economics by proposing Nyai’s religious social capital as a culturally grounded model of women’s empowerment within pesantren economies. This model broadens discussions of Sharia-based socio-economic empowerment by linking gender agency, local religious authority, and inclusive economic development in emerging Muslim economies.